2011
DOI: 10.1080/18811248.2011.9711723
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sensors for On-Line Monitoring of Nonmetallic Impurities in Liquid Sodium

Abstract: Sensors for on-line monitoring of hydrogen and carbon in sodium and hydrogen in argon cover gas circuits over sodium have been developed. The performance of these sensors in fast breeder test reactor (FBTR) and large sodium facilities is evaluated. A sensor for monitoring oxygen in sodium is under development. The in-sodium electrochemical hydrogen sensors are found to detect about 10 ppb increase in hydrogen concentration over a background of 50 ppb. The cover gas hydrogen monitoring sensor system is found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…3c) with In/In 2 O 3 as reference electrode and tested in static sodium. These sensors showed near theoretical output corresponding to oxygen concentration in sodium at 723 K. 53 However, their lifetimes varied between 24 and 720 h and the failure was observed at the metal-ceramic interface region. This suggested that probably stress prevailed at the interface, which led to the failure of the ceramic.…”
Section: Recent Efforts Made In Igcar For the Development Of In-sodiummentioning
confidence: 99%
“…3c) with In/In 2 O 3 as reference electrode and tested in static sodium. These sensors showed near theoretical output corresponding to oxygen concentration in sodium at 723 K. 53 However, their lifetimes varied between 24 and 720 h and the failure was observed at the metal-ceramic interface region. This suggested that probably stress prevailed at the interface, which led to the failure of the ceramic.…”
Section: Recent Efforts Made In Igcar For the Development Of In-sodiummentioning
confidence: 99%
“…The state-of-the-art yttria-doped thoria (YDT) electrolyte fulfills the chemical stability requirements in a sodium environment [8][9][10][11][12][13][14][15][16][17][18]. However, the solid electrolyte exhibits many drawbacks: it is a nuclear material, this oxide is difficult to supply, it is very expensive [19], the conventional sintering method requires temperatures of higher than 2000°C and the material's mechanical resistance is poor.…”
Section: Introductionmentioning
confidence: 99%